Antithrombotic activities of fucosylated chondroitin sulfates and their depolymerized fragments from two sea cucumbers. (5th November 2016) - Liu, Xiaoxiao; Hao, Jiejie; Shan, Xindi; Zhang, Xiao; Zhao, Xiaoliang; Li, Qinying; Wang, Xiaojiang; Cai, Chao; Li, Guoyun; Yu, Guangli
Highlights: FCSs structures from two sea cucumbers were characterized. Anticoagulant and anti-thrombotic activity were compared in vitro and in vivo . FCSs had similar activity with different sulfation patterns. Sulfation patterns might not affect anti-thrombotic activity as much as molecular weight. Abstract: Fucosylated chondroitin sulfate (FCS), a glycosaminoglycan extracted from the body wall of sea cucumber, is a promising antithrombotic agent. The chemical structures of FCS c isolated from sea cucumber Cucumaria frondosa and its depolymerized fragment (dFCSc) were characterized for the first time. Additionally, anticoagulant and antithrombotic activities were evaluated in vitro and in vivo . The results demonstrated that dFCS c exhibited better antithrombotic-hemorrhagic ratio than native FCS c on the electrical induced arterial thrombosis model in rats. Compared to FCS t obtained from Thelenota ananas, FCS c possessed different sulfation patterns but similar antithrombotic effects. Therefore, sulfation pattern of FCS might not affect anticoagulation and antithrombosis as much as molecular weight may. Our results proposed a new point of view to understand the structure-activity relationship of FCS as alternative agents.